1987
DOI: 10.1063/1.339770
|View full text |Cite
|
Sign up to set email alerts
|

Growth of single-crystal TiN/VN strained-layer superlattices with extremely high mechanical hardness

Abstract: Single-crystal TiN/VN strained-layer superlattices (SLS’s) with layer thicknesses lTiN =lVN =λ/2 (where λ is the period of the superlattice) ranging from 0.75 to 16 nm have been grown on MgO(100 ) substrates by reactive magnetron sputtering. Cross-sectional transmission electron microscopy (TEM) and x-ray diffraction examinations showed that the films were single crystals exhibiting coherent interfaces and several orders of superlattice reflections. There was no evidence in either plan-view or cross-sectional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
237
0
4

Year Published

1999
1999
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 723 publications
(250 citation statements)
references
References 17 publications
9
237
0
4
Order By: Relevance
“…This shows that no direct correlation can be drawn between the micro-hardness properties and the sublayer inter-diffusion phenomena. Such a tendency was previously confirmed on TiN/NbN superlattices by Yashar and Sproul [7] and by other authors [8,9] for different carbide and nitride PVD deposited superlattice coatings. Anderson and co-authors also observed a similar micro-hardness evolution for metallic structure like Cu/Ni multilayers [10].…”
Section: Layered Structuresupporting
confidence: 64%
See 1 more Smart Citation
“…This shows that no direct correlation can be drawn between the micro-hardness properties and the sublayer inter-diffusion phenomena. Such a tendency was previously confirmed on TiN/NbN superlattices by Yashar and Sproul [7] and by other authors [8,9] for different carbide and nitride PVD deposited superlattice coatings. Anderson and co-authors also observed a similar micro-hardness evolution for metallic structure like Cu/Ni multilayers [10].…”
Section: Layered Structuresupporting
confidence: 64%
“…4) leads to the following general expression associated to a mean "composite" friction coefficient. (8) Applied to the bi-layer system, the following simplified formulation is then deduced. …”
Section: Composite Friction Modelmentioning
confidence: 99%
“…8 Also two-phase nanocrystalline materials in the form of multilayers exhibit an increased hardness compared to their constituents due to the difference in elastic properties between the layers that hinder dislocation motion, 9 most clearly seen in nanoscale multilayers. 10,11 The decomposition of metastable single-phase films can also act to improve the hardness at elevated temperature as a two-phase structure is formed. The most studied of these is the TiAlN system where age hardening upon annealing of thin films was first observed.…”
Section: Introductionmentioning
confidence: 99%
“…In studies on the TiN/VN [40] and TiN/NbN [41] systems, maximum hardness enhancement can be observed for a periodicity between 4 and 8 nm, as illustrated in Figure 2.6 taken from [42]. The hardness enhancement mechanism was found to be the hindering of dislocation movement across sharp interfaces by a mismatch between the elastic moduli of the layers [42].…”
Section: Multilayer Nanostructured Coatings -Nanolaminatesmentioning
confidence: 95%